Development of a sustainable agro-pastoral system in the dry areas of Northeast Asia (JIRCAS, 2013)
Contents: Characterization of agriculture and livestock farming in semi-arid areas of Mongolia and Inner Mongolia, investigation of economic conditions for sustainable livestock management in commonly used pastures in Mongolia and privately owned pasture in Inner-Mongolia, ...